Immunomodulating activities of soluble synthetic polymer-bound drugs - Ríhová, Blanka (Advanced drug delivery reviews, 2002)
The introduction of a synthetic material into the body always affects different body systems, including the defense system. Synthetic polymers are usually thymus-independent antigens with only a limited ability to elicit antibody formation or to induce a cellular immune response against them. However, there are many other ways that they influence or can be used to influence the immune system of the host. Low-immunogenic water-soluble synthetic polymers sometimes exhibit significant immunomodulating activity, mainly concerning the activation/suppression of NK cells, LAK cells and macrophages. Some of them, such as poly(ethylene glycol) and poly[N-(2-hydroxypropyl)methacrylamide], can be used as effective protein carriers, as they are able to reduce the immunogenicity of conjugated proteins and/or to reduce non-specific uptake of liposome/nanoparticle-entrapped drugs and other therapeutic agents. Recently, the development of vaccine delivery systems prepared from biodegradable and biocompatible water-soluble synthetic polymers, microspheres, liposomes and/or nanoparticles has received considerable attention, as they can be tailored to meet the specific physical, chemical, and immunogenic requirements of a particular antigen and some of them can also act as adjuvants.
Keywords: doxorubicin; vakcíny; protinádorové látky; Neoplasms; membránové glykoproteiny; ligand Fas; methakryláty; Drug Carriers; rozpustnost; Polymers; Adjuvants, Immunologic; Animals; lidé; Vaccines; polymery; Humans; adjuvancia imunologická; zvířata; buňky NK; makrofágy; Membrane Glycoproteins; nádory; Killer Cells, Natural; nosiče léků; Macrophages; Methacrylates; Doxorubicin; Fas Ligand Protein; Antineoplastic Agents; Solubility